2022
DOI: 10.1002/ldr.4212
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the permafrost environment under dual impacts of climate change and human activities in the Hola basin, northern Da Xing'anling Mountains, Northeast China

Abstract: The Hola basin in the northern Da Xing'anling Mountains in Northeast China has been extensively developed for coal mining since the 1980s, resulting in a significantly degrading permafrost environment. However, the changing thermal state of permafrost under the boreal forest remains unclear. Based on ground temperature records from nine monitoring boreholes at three areas (disturbed, backfilled, and undisturbed areas) from 2015 to 2020, the thermal state of permafrost under the dual influences of climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Thus, the model is deemed to have an accurate fit. In this paper, 50 borehole data (MAGT) were collected from permafrost regions of Northeast China between 2000 and 2020 [51][52][53][54][55][56]. The data were divided into 25 groups each from the 2000s and 2010s and compared with the TTOP of the same period in the present study.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the model is deemed to have an accurate fit. In this paper, 50 borehole data (MAGT) were collected from permafrost regions of Northeast China between 2000 and 2020 [51][52][53][54][55][56]. The data were divided into 25 groups each from the 2000s and 2010s and compared with the TTOP of the same period in the present study.…”
Section: Model Evaluationmentioning
confidence: 99%
“…(When the borehole-measured MAGT is greater than 0 °C, that temperature represents the average temperature of the borehole and there is no permafrost at that borehole location). In this paper, 50 borehole data (MAGT) were collected from permafrost regions of Northeast China between 2000 and 2020 [51][52][53][54][55][56]. The data were divided into 25 groups each from the 2000s and 2010s and compared with the TTOP of the same period in the present study.…”
Section: Model Evaluationmentioning
confidence: 99%
“…γ t xy is the shear strain caused by the decrease of volume caused by frozen soil thawing. Substituting Equation (9) into Equation (8), and shown as Equation (10): Introducing the linear thermal expansion coefficient, making ε t y •=•α•(T − T C ), then α can be expressed as Equation (11):…”
Section: Physics Modelsmentioning
confidence: 99%
“…Permafrost in northeast of China covers about 3.1 × 10 5 km 2 [8], and a large number of asphalt pavement and fewer concrete pavement highways were constructed on it, such as the Beijing-Mohe highway (G111), Dandong-Altay highway (G331), and Jiayin-Linjiang highway (G222), as shown in Figure 1. Researchers have shown that the global permafrost temperature increased by 0.29 ± 0.12 • C between 2007 to 2016 [9], and the permafrost in northeast of China has increased by 0.2-0.5 • C during the past six years [10]. It is obvious that the permafrost in Northeast of China is dying, and the aera is shrinking and the north boundary of Eurasian permafrost is moving at a rate of 3.6 × 10 4 km 2 per decade [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rising air and soil temperatures favor population and agriculture expansion in cold regions [ 26 , 27 ]. The northeast plain is one of the main grain-producing regions in China, as well as the second-largest extent of permafrost and the most important region of latitudinal permafrost in China [ 28 , 29 ]. However, the existing studies on PTEs in permafrost soils in China mainly focused on the Qinghai–Tibet Plateau [ 30 , 31 , 32 , 33 , 34 ], while studies in northeast China are rare.…”
Section: Introductionmentioning
confidence: 99%